Repurposing a Bacterial Quality Control Mechanism to Enhance Enzyme Production in Living Cells. Issue 6 (27th March 2015) - Boock, Jason T.; King, Brian C.; Taw, May N.; Conrado, Robert J.; Siu, Ka-Hei; Stark, Jessica C.; Walker, Larry P.; Gibson, Donna M.; DeLisa, Matthew P.
Abstract: Heterologous expression of many proteins in bacteria, yeasts, and plants is often limited by low titers of functional protein. To address this problem, we have created a two-tiered directed evolution strategy in Escherichia coli that enables optimization of protein production while maintaining high biological activity. The first tier involves a genetic selection for intracellular protein stability that is based on the folding quality control mechanism inherent to the twin-arginine translocation pathway, while the second is a semi-high-throughput screen for protein function. To demonstrate the utility of this strategy, we isolated variants of the endoglucanase Cel5A, from the plant-pathogenic fungus Fusarium graminearum, whose production was increased by as much as 30-fold over the parental enzyme. This gain in production was attributed to just two amino acid substitutions, and it was isolated after two iterations through the two-tiered approach. There was no significant tradeoff in activity on soluble or insoluble cellulose substrates. Importantly, by combining the folding filter afforded by the twin-arginine translocation quality control mechanism with a function-based screen, we show enrichment for variants with increased protein abundance in a manner that does not compromise catalytic activity, providing a highly soluble parent for engineering of improved or new function. Graphical Abstract: Highlights: Two-tiered directed evolution strategy enables 30-fold enhancement of protein production. The first tier involves genetic selection for intracellular protein stability. The second tier involves semi-high-throughput screen for protein function. Isolated variants show increased protein abundance and uncompromised catalytic activity.